La pratique réflexive et la justice sociale : que disent les futurs administrateurs et les directions d’établissement scolaire francophone minoritaire au Manitoba ? - Archambault, Hélène Louise; Piquemal, Nathalie (Canadian Journal of Education/Revue canadienne de l’éducation, 2025)
In this article, we explore reflective practice from the perspective of future administrators and principals in Manitoba’s minority francophone school context. Using a qualitative methodology centred on individual interviews semi-directed by narratives of practice, we examine the following angles: questioning, intervention, the link between theory and practice, and the tension between diversity and equity. Findings indicate that future school administrators and principals develop approaches that range from general reflection on certain pedagogical approaches to critical, even self-critical, reflection on practices committed to equity.